Analysis of Factors Affecting The Implementation Of Health Promotion Programs For Pulmonary Tb Patients At Grandmed Hospital Lubuk Pakam In 2024 - Jansfianti, Mira; Rotua Sumihar Sitorus; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2025)
Tuberculosis (TB) is still a major health problem globally, due to serious health disorders in the community and the incidence of this disease increases every year. Currently, it is estimated that 1 in every 3 TB cases have not been detected by the Case Detection Rate (CDR) program, which is known from national data showing that CDR in Indonesia from 2012-2014 has decreased, namely case discovery in 2012 was 61%, and in 2014 the case discovery rate was 46%. The purpose of this study was to Analyze Factors Influencing the Implementation of the Pulmonary TB Patient Health Promotion Program at the Grandmed  Lubuk Pakam Hospital in 2024. This study is a qualitative descriptive study. The results of this study are that the implementation of the pulmonary TB patient health promotion program in hospitals is influenced by various interrelated factors, namely individual factors, the environment, health systems, policies, and health workers. Individual factors such as knowledge, socio-economic conditions, and treatment compliance determine the extent to which patients can accept and carry out health recommendations. Environmental factors, including social stigma and family or community support, also influence patient motivation and openness to health education. From the health system side, the existence of an effective information system and guaranteed drug availability are crucial technical supports. Meanwhile, the success of the program is highly dependent on management policies and the design of a structured and sustainable promotion program. The conclusion is that the role of health workers through quality communication and education greatly determines the effectiveness of information delivery and changes in patient behavior. Therefore, optimal implementation of health promotion requires a comprehensive and collaborative approach from all of these factors to support sustainable TB control efforts in hospitals.